Improved Weakly Conditionally Stable Finite-Difference Time-Domain Method - Chen , Juan (Applied Computational Electromagnetics Society Journal (ACES), 2022)
To circumvent the inaccuracy in the implementation of the perfect-electric-conductor (PEC) condition in the weakly conditionally stable finite-difference time-domain (WCS-FDTD) method, an improved weakly conditionally stable (IWCS) FDTD method is presented in this paper. In this method, the solving of the tridiagonal matrix for the magnetic field component is replaced by the solving of the tridiagonal matrix for the electric field components; thus, the perfectelectric- conductor (PEC) condition for the electric field components is implemented accurately. The formulations of the IWCS-FDTD method are given, and the stability condition of the IWCSFDTD scheme is presented analytically. Compared with the WCS-FDTD method, this new method has higher accuracy in the implantation of the PEC condition, which is demonstrated through numerical examples.